Visual Interpretation Of Love In Mohammed Hamaki's Layla Video Clip - Nur Afifah (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2025)
This article aims to examine the visual interpretation of love through audiovisual representations applied to Layla's music video. Layla is an Amiyyah Arabic song sung by Mohammed Hamaki. In discussing the audiovisual meaning, the researcher examines the cultural meaning of the Layla video clip and its love symbols through Peirce's triadic framework. This research was descriptive and qualitative with the use of listening technique with tapping. In this study, a semiotic theory by Charles Sanders Peirce was used, with an approach by Stuart Hall’s theory of representattion. The results showed that the emotional and cultural meaning were found within the triadic semiotic argument of Peirce in Layla's audiovisual work. These findings provide a more comprehensive understanding of Peirce's semiotic theory as applied to literature and audiovisual art, especially in video clips.